Own and Possess―A Corpus Analysis - Nordlund, Marie (Nordic Journal of English Studies, 2009)
This study is a corpus-based analysis of the verbs own and possess, which are two of the verbs that are used to express possession and ownership in English. The results show that there are areas of overlapping use as well as areas where only one of the two is a valid option. It has also been shown that own has a legal feature at its core and is predominantly used to express ownership. The most frequent usage of possess, on the other hand, is that of describing that someone or something has a quality or property of some kind. This difference also has consequences for what kinds of entities appear as the subject and object arguments of the verbs.